What helps volunteers to continue with their work? - G. Marincowitz; C. Jackson; S. Fehrsen (South African Family Practice)
Aim: The aim of the study was to understand what volunteers perceived to be the factors helping them to continue working as volunteers, thereby assisting project leaders to improve the recruitment procedures, as well as quality of service, in the future.